2023
DOI: 10.3390/tropicalmed8040189
|View full text |Cite
|
Sign up to set email alerts
|

One Health Approach on Dog Bites: Demographic and Associated Socioeconomic Factors in Southern Brazil

Abstract: Despite being an important public health issue, particularly due to rabies, dog bites and associated risk factors have rarely been assessed by health services from a One Health perspective. Accordingly, the present study aimed to assess dog biting and associated demographic and socioeconomic risk factors in Curitiba, the eighth-largest Brazilian city with approximately 1.87 million people, based on the post-exposure prophylaxis (PEP) rabies reports between January/2010 and December/2015. The total of 45,392 PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…37 [91] Chi-squared tests [41] To identify spatial patterns, relationships, and trends in dog biting incidents.…”
Section: [89]mentioning
confidence: 99%
See 3 more Smart Citations
“…37 [91] Chi-squared tests [41] To identify spatial patterns, relationships, and trends in dog biting incidents.…”
Section: [89]mentioning
confidence: 99%
“…Few papers using spatial analysis [25], [27], [47], [50] [14], [91], [92], [20], [21], [23], [27], [29], [32] Table 2.…”
Section: Year Of Studies and Publicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, a disturbingly higher than usual number of human deaths by dog attacks was reported in 2022 in the USA, highlighting that unhealthy human-dog interactions worsened during the COVID-19 pandemic, probably associated with inadequate breeding and rearing and inappropriate socialization ( 12 ). Not surprisingly, a recent study by our research group in Curitiba, Brazil has also shown that dog bites should also be approached from a One Health perspective, as such accidents involve human, animal, and environmental associated risk factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%